How adsorbates alter the metallic behavior of quasi-1D electron systems of the Si(5\hspace0.167em5\hspace0.167em3)-Au surface - Tzschoppe, Michael; Huck, Christian; Hötzel, Fabian; Günther, Benjamin; Gade, Lutz H.; Pucci, Annemarie (Journal of physics. Condensed matter, 2019)
The plasmonic signals of quasi-1D electron systems are a clear and direct measure of their metallic behavior. Due to the finite size of such systems in reality, plasmonic signals from a gold-induced superstructure on Si(5 5 3) can be studied with infrared spectroscopy. The infrared spectroscopic features have turned out to be extremely sensitive to adsorbates. Even without geometrical changes of the surface superstructure, the effects of doping, of the adsorbate induced electronic surface scattering, and of the electronic polarizability changes on top of the substrate surface give rise to measurable changes of the plasmonic signal. Especially strong changes of the plasmonic signal have been observed for gold, oxygen, and hydrogen exposure. The plasmonic resonance gradually disappears under these exposures, indicating the transion to an insulating behavior, which is in accordance with published results obtained from other experimental methods. For C70 and, as shown here for the first time, TAPP-Br, the plasmonic signal almost retains its original intensity even up to coverages of many monolayers. For C70, the changes of the spectral shape, e.g. of electronic damping and of the resonance position, were also found to be marginal. On the other hand, TAPP-Br adsorption shifts the plasmonic resonance to higher frequencies and strongly increases the electronic damping. Given the dispersion relation for plasmonic resonances of 1D electron systems, the findings for TAPP-Br indicate a push-back effect and therefore stronger confinement of the free charge carriers in the quasi-one-dimensonal channel due to the coverage by the flat TAPP-Br molecules. On the gold-doped Si(5 5 3)-Au surface TAPP-Br acts as counter dopant and increases the plasmonic signal.
Gesehen am 23.05.2019